Investigation of the effect of assertive skills training on attitude towards substance abuse in Tehran and Allame Tabatabayee university students - Hamid reza Daemi; Faramarz Sohrabi; Seyed Fateme Moghimi (Drug Control Headquarters, Research and Education Office, 2009)
Objectives: The present research investigated the effect of assertive skills training on attitude towards substance abuse in Tehran and Allame Tabatabayee university students. Methods: The sample of this research includes 76 university students (39 experimental,37 control) From two university by using random selection sampling method. They pre tested and then choose Experimental group Tehran university students. Experimental group have been thought assertive skills training in 8 sessions, but the control group received no variable. Finding: At the end, both of them were post test and experimental group were follow up tested. Discussion: The data were analyzed by applying covariance test and T test. The result indicated That assertive skills training are effective in changing university student's attitudes towards substance abuse.